The Effect Of Jicama Flour Substitution On The Quality Of Soft Cookies - Ningrum, Wulan Salwa; Gusnita, Wiwik; Holinesti, Rahmi; Anggraini, Ezi (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
Soft cookies are a food made from a mixture of wheat flour, granulated sugar, palm sugar, butter, and others. In this research, the main ingredient for making soft cookies was substituted with jicama flour. Jicama flour comes from jicama fruit which is very easy to get in Padang City because Padang City is one of the areas with a lot of jicama production. According to data from BPS Padang, the yam farming area reaches 128 ha with a production output of 192 quintals/ha/year with a total of 2,208 tons/year. So from these data it can be seen that jicama has great potential for optimization of processing, especially for jicama fruit which is no longer attractive to buyers because the color of the skin is starting to turn black. This research aims to analyze the effect of 15%, 30% and 45% substitution of jicama flour on the quality of the shape, color, aroma, texture and taste of the soft cookies produced. And also to reduce imports of wheat flour which have increased greatly. This research was conducted using a pure experimental method (true experiment) with a completely randomized design method. The data collection technique involves observation with the help of an organoleptic test sheet with 3 expert panelists. The data obtained were tabulated in table form and then analysis of variance (ANOVA) was carried out if they were significantly different followed by the Duncan test. Jicama flour substitution affects the quality of shape (round and neat), color (brown), aroma (fragrant), texture (brittle and soft on the inside), and taste (sweet).